Molecular mechanisms governing aerobic granular sludge processes - Zhou, Yan (2015)
The aerobic granular sludge process is a promising technology for wastewater treatment. The formation and structure of aerobic granules are traditionally thought to depend highly on selection pressures, while the underlying molecular mechanisms are unclear. It is well known that bacteria coordinate their behavior using small signaling molecules, known as quorum sensing (QS). This paper is an attempt to provide updated information on QS mechanisms governing granular sludge processes. It is shown that QS-mediated cellular communication has a significant role throughout aerobic granulation, including granule development, structural stability and integrity maintenance. Such understanding is helpful for developing novel aerobic granular sludge processes.